Sequence Analysis of Changes in Microbial Composition in Different Milk Products During Fermentation and Storage - Zalewska, Barbora; Kaevska, Marija; Slana, Iva (Current microbiology, 2018)
The objective of this study was to analyze the changes in the microbiota of milk products during fermentation and storage. Two kinds of Yoghurt, one Kefir, and one Acidophilus milk were observed during the fermentation process and storage using 16S rDNA amplicon sequencing. Cow's, goat's, raw and pasteurized milk were also examined. The most represented organisms in all manufactured products were shown to be those of the phylum Firmicutes. In some products, Proteobacteria, Bacteroidetes and Actinobacteria were also present in high amounts.
Keywords: Food Storage; mléko; Sequence Analysis, DNA; RNA, Ribosomal, 16S; DNA, Bacterial; Bacteria; společenstvo; skladování potravin; Fermented milk products; kysané mléčné výrobky; DNA, Ribosomal; skot; DNA bakterií; Cultured Milk Products; Lactic acid bacteria; Sequencing method; RNA ribozomální 16S; Storage; zvířata; fylogeneze; ribozomální DNA; fermentace; Cattle; sekvenční analýza DNA; Milk; Biota; Fermentation; Goats; Phylogeny; kozy; Animals